Environmental & architectural phenomenology. Vol. 21, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2010)
Vol. 21, No. 1, Winter 2010 (includes “items of interest,” “citations received,” a conference review by Dylan Trigg, and essays by Alvin Holm, John Cameron, Bruce Janz & Phil Stafford).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals